Individualized preparatory staged training model for junior female footballers - Vyprikov, D. V.; Shutova, T. N.; Bodrov, I. M.; Golubnichiy, S. P. (Theory and Practice of Physical Culture, 2019)
The study was intended to develop and test benefits of an individualized conditioning, special preparatory and pre-season training model for junior women football players. The model combines specific and unspecific training tools applicable in the preparatory training periods. Sampled for the model testing experiment were the 12-14 year old players (n=40) from Snezhana-Kotelniki Football Club split up into Experimental and Reference Groups of 20 people each; with the Reference Group trained in the standard system and Experimental Group trained as required by the new individualized staged training model. The training process was designed on an individualized physical training-stage-specific basis. The individual progress was tested by the following tests: different pass options with the error rates; ball repossessions; dribbling attempts; ball control times; and the head strikes on goal. The new model was tested particularly beneficial with the following shares of the unspecific and specific training components (respectively): 75% and 25% for the conditioning stage; 80% and 20% for the special preparatory stage; and 86% and 14% for the pre-season stage.